2020
DOI: 10.1016/j.isci.2020.101480
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Microenvironment Induces DNMT1 Suppression and Indolence of Metastatic Cancer Cells

Abstract: Brain metastasis is an ineffective process, and many cancer cells enter into an indolent state following extravasation in the brain. Single cell RNA sequencing of melanoma brain metastases reveals that non-proliferating brain metastatic melanoma cells exhibit a pattern of gene expression associated with inhibition of DNA methyltransferase 1 (DNMT1). The brain microenvironment, specifically the combination of reactive astrocytes and mechanically soft surroundings, suppressed DNMT1 expression in various cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…In the early stage of brain metastasis, when the survival of cancer cells is unstable, it has been reported that cancer cells slow down cell cycle progression and enhance apoptosis-resistant survival signals. This switching is thought to involve a mechanism in which a component secreted by peripheral astrocytes suppresses DNMT1, a methyltransferase of cancer cells [ 21 ]. It is suggested that there is a mechanism by which the responsiveness of peripheral astrocytes is dynamically altered upon some stimuli or oxidative stress loading and that such changes are first manifested in metabolomic shifts.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of brain metastasis, when the survival of cancer cells is unstable, it has been reported that cancer cells slow down cell cycle progression and enhance apoptosis-resistant survival signals. This switching is thought to involve a mechanism in which a component secreted by peripheral astrocytes suppresses DNMT1, a methyltransferase of cancer cells [ 21 ]. It is suggested that there is a mechanism by which the responsiveness of peripheral astrocytes is dynamically altered upon some stimuli or oxidative stress loading and that such changes are first manifested in metabolomic shifts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dysregulation of these cells can promote tumor growth and metastasis. Recent studies demonstrate that the relationships between cancer cells and their surrounding microenvironments affect cancer cell survival, growth, proliferation, epithelial-mesenchymal transition (EMT), and metastasis ( 4 ). Thus, the modulation of the TME as a target for clinical applications is an area of interest in cancer treatments.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that astrocytes and the soft surrounding microenvironment suppressed DNA methyltransferase 1 and kept cancer cells in dormant states. 26 These mechanisms could be related to our model. Moreover, our results showed that varied cell cycle patterns of metastatic tumors were observed in the same organ.…”
Section: Discussionmentioning
confidence: 72%